2019
DOI: 10.1093/biolinnean/blz102
|View full text |Cite
|
Sign up to set email alerts
|

Water turbidity affects melanin-based coloration in the gudgeon: a reciprocal transplant experiment

Abstract: Human activities cause rapid eutrophication and increased water turbidity in aquatic ecosystems, but their effects on fish communication and colour signals remain of debate. In particular, melanin-based coloration in fish has been understudied, because it was believed to be less costly to display than carotenoid-based colours. Here, we measured the phenotypic divergence of melanin-based coloration in 17 populations of gudgeon (Gobio occitaniae) along a turbidity gradient. We also tested the short-term plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Many studies have shown that lighting habitats correlate with the respective color patterns (e.g., Reimchen 1989 ; Scott 2001 ; Fuller 2002 ; Novales Flamarique et al 2013a ; Giery and Layman 2017 ; Côte et al 2019 ). We also found substantial differences between the color patterns at longer but not at shorter wavelengths of males of the tea-stained and clear-water habitat type ( Table 1 ) that correlate with the lighting habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that lighting habitats correlate with the respective color patterns (e.g., Reimchen 1989 ; Scott 2001 ; Fuller 2002 ; Novales Flamarique et al 2013a ; Giery and Layman 2017 ; Côte et al 2019 ). We also found substantial differences between the color patterns at longer but not at shorter wavelengths of males of the tea-stained and clear-water habitat type ( Table 1 ) that correlate with the lighting habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal transplant experiments are often used to test how a population is affected by the environment. Non-zero reaction norms can be taken as either evidence for plasticity (e.g., Côte et al 2019; Walter et al 2021) or for local adaptation (e.g., Barton et al 2020; Martin et al 2021). However, the interpretation of reaction norms obtained in reciprocal transplant experiments may lead to opposite conclusions depending on whether the assessed trait is an adaptive trait or a fitness-indicator trait.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the change of color-based signals in response to visually challenging environments has been demonstrated only in a handful of studies, and limited to the context of adult signaling. In gudgeon fish, a two-week transplant experiment showed the overall expression of melanin decreased in turbid conditions, leading to lighter colored fishes (i.e., economy of pigments hypothesis; Côte et al, 2019). We hypothesize that increased turbidity levels will induce a "relaxed" phenotype where tadpoles do not express camouflage/disruptive coloration despite the potential presence of predators.…”
Section: Environmentally Induced Phenotypic Adaptations and Their Cascading Effectsmentioning
confidence: 92%